Can the use of neuromuscular electrical stimulation be improved to optimize quadriceps strengthening? - Glaviano, N. R.; Saliba, S. (Sports Health: A Multidisciplinary Approach, 2016)
Context: Neuromuscular electrical stimulation (NMES) is a common modality used to retrain muscles and improve muscular strength after injury or surgery, particularly for the quadriceps muscle. There are parameter adjustments that can be made to maximize the effectiveness of NMES. While NMES is often used in clinical practice, there are some limitations that clinicians should be aware of, including patient discomfort, muscle fatigue, and muscle damage.